Ruling of Yazid bin Abdul-Malik 101-105 AH / 720-724 CE - Kalil Huseen (آداب الرافدين, 1985)
This research addresses the period of the rule of the Umayyad caliph Yazid bin Abdul Malik, which extends from the year 101 AD until the year 105 AH. The research is an attempt to evaluate the internal and external policies of this caliph, especially as he pursued a policy that differs in its main lines from that of his predecessor Omar bin Abdulaziz 99-101 AH. The policy of Yazid bin Abdul Malik is still being criticized by historians and researchers. It needs to clarify its features and remove the ambiguity surrounding the era in which this caliph ruled. The search - then - is an effort aimed at shedding light on the events that took place in the succession of Yazid bin Abdul Malik, the method of his rule and the mentality that shaped political, economic and administrative decisions. Through what the original sources provide us with historical information, the research attempts to provide an objective picture that is closer to historical reality and within the rules of modern historical criticism and scientific analysis, which impose on us to move away from prejudices and prejudices as they do not serve the discreet historical truth sought by historical research.